Hydraulic erosion patterns downstream of corrugated aprons: investigating free and submerged jet effects - Mumtaz, Mohd Aamir; Elgamal, Mohamed H.; Farouk, Mohamed I.; Siddiqui, Md Irfanul Haque (Frontiers in Environmental Engineering, 2024)
The experimental evaluation of the performance of a corrugated apron under free flow subcritical and submerged conditions was conducted, with a focus on scour patterns over the apron. Comparative analysis with a smooth rigid apron revealed an increase in scour depth upon the application of the corrugated apron under free and submerged jet flow conditions. The implementation of a corrugated apron resulted in a considerable reduction in scour depth and length compared to a smooth rigid apron. The maximum reduction in scour depth and length amounted to 79% and 83%, respectively, while the minimum reduction observed was 13% in scour depth and 11% in scour length. Additionally, investigations into velocity and turbulence characteristics over both smooth and corrugated aprons were conducted. It was observed that the rate of turbulence intensity increase within the scour hole due to the presence of a smooth apron surpassed that of the corrugated apron. Scour downstream of the corrugated apron exhibited distinct delineations, including regions of jet diffusion, transition, acceleration, and a recirculating zone near the bed of the scour hole.